The Influence of Academic Self-Efficacy and Christian Values Learning on Bullying Behavior Tendencies at SMA Kristen 2 Binsus Tomohon - Tigau, Zefanio Laodikia; Mamhit, Meyke M.; Siang, Jhoni Lagun (International Journal of Education, Information Technology, and Others, 2025)
ABSTRACT This study aims to describe and analyze the influence of Academic Self-Efficacy on the tendency of Bullying Behavior at SMA Kristen 2 Binsus Tomohon; to describe and analyze the influence of Christian Values Learning on the tendency of Bullying Behavior at SMA Kristen 2 Binsus Tomohon; and to describe and analyze the simultaneous influence of Academic Self-Efficacy and Christian Values Learning on the tendency of Bullying Behavior at SMA Kristen 2 Binsus Tomohon. This research employed a quantitative approach using an associative-causal type of reaserch. The population consisted of 187 students, with a sample size of 65 students selected through probability sampling using the simple random sampling technique. The findings of this study indicate that: (1) there is a positive influence of Academic Self-Efficacy (X1) on Bullying Behavior (Y); (2) there is a positive influence of Christian Values Learning (X2) on Bullying Behavior (Y); and (3) there is a simultaneous positive influence of Academic Self-Efficacy (X1) and Christian Values Learning (X2) on Bullying Behavior (Y). Academic Self-Efficacy and Christian Values Learning, both individually and collectively, have a significant positive impact in reducing the tendency of Bullying Behavior. The higher the students’ confidence in their academic abilities combined with their understanding and application of Christian values, the lower their tendency to engage in bullying behavior. Keywords: Academic Self-Efficacy, Christian Values Learning, Bullying Behavior